Accounts for the groups SL(2,U), U = 41 and 43 - Niran Sabah; Sherouk Awad Khalaf (Al-Qadisiyah Journal of Pure Science, 2021)
The  circular retail  for  the  groups  (2,)  where    =  41  and  43  compute  in  this  paper  from  the  ordinary  character table  and  the  character table (ch.t.) of  rational  representations (r.rep.) for  each  group.